First direct observation of muon antineutrino disappearance. - Adamson, P; Andreopoulos, C; Auty, D; Ayres, D; Backhouse, C; Barr, G; Bishai, M; Blake, A; Bock, G; Boehnlein, D; Bogert, D; Cavanaugh, S; et al. (2011)
This Letter reports the first direct observation of muon antineutrino disappearance. The MINOS experiment has taken data with an accelerator beam optimized for ν(μ) production, accumulating an exposure of 1.71 × 10²⁰ protons on target. In the Far Detector, 97 charged current ν(μ) events are observed. The no-oscillation hypothesis predicts 156 events and is excluded at 6.3σ. The best fit to oscillation yields |Δm²| = [3.36(-0.40)(+0.46)(stat) ± 0.06(syst)] × 10⁻³ eV², sin²(2θ) = 0.86(-0.12)(+0.11)(stat) ± 0.01(syst). The MINOS ν(μ) and ν(μ) measurements are consistent at the 2.0% confidence level, assuming identical underlying oscillation parameters.